IMPROVEMENT OF STUDENT LEARNING ACTIVITIES IN IPSKELAS V LESSONS THROUGH THE IMPLEMENTATION OF NUMBER HEAD TOGETHER (NHT) LEARNING MODELS AT SDN 017 BATURIJAL HULU - eprinita S.Pd.SD (el-Ibtidaiy:Journal of Primary Education, 2020)
This study aims to determine the application of the cooperative learning model with the number head together (NHT) type to increase learning activeness in fifth grade students in social studies subjects. This research was conducted at SDN 017 Baturijal Hulu in the 2019/2020 school year. This research was conducted in two cycles, in the first cycle student learning outcomes achieved 80% classical completeness and there was an increase in the second cycle reaching 100%. Based on these results, it can be concluded that the application of the number head together (NHT) learning model can improve student learning outcomes in social studies class V SDN 017 Baturijal Hulu. So, based on this research, it can be concluded that the NHT type of cooperative learning model can increase student learning activeness in the social studies subject for class V SDN 017 Baturijal Hulu.